(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
This paper explores a client’s experiences of being-out-of-time, and their location of an agentic and interpersonal version of themselves in an imagined past time-world. I use the work of Eugène Minkowski to explore these experiences and provide an alternative framework for working with temporality to that offered by Heidegger and psychotraumatology.